External Devaluations : Are Small States Different? - Acevedo Mejia, Sebastian (IMF Working Papers; Working Paper ;, 2015)
The paper investigates whether the macroeconomic effects of external devaluations have systematically different effects in small states, which are typically more open and less diversified than larger peers. Through several analytical approaches -- DSGE model, event study, and regression analysis -- it finds that the effects of devaluation on growth and external balances are not significantly different between small and large states, with both groups equally likely to experience expansionary or contractionary outcomes. However, the transmission channels are different: devaluations in small states are more likely to affect demand through expenditure compression, rather than expenditure-switching channels. In particular, consumption tends to fall more sharply in small states due to adverse income effects, thereby reducing import demand. Policy conclusions point to the importance of social safety nets, complementary wage and antiinflation policies, investment-boosting reforms, and attention to potential adverse balance sheet effects to ensure positive outcomes.